Funcionalidades elétricas mediadas por defeitos em óxidos semicondutores do tipo-p - Silva, Ana Luiza Costa (2023)
Structural defects, such as point defects, play an important role in the electrical transport in semiconductor oxide films. This work presents a systematic study of photoconductivity at room temperature in thin films of Co3O4 as well as ZnO doped with different sodium contents. Polycrystalline samples grown by spray pyrolysis exhibit positive photoconductivity. Both Co3O4 and ZnO films underwent thermal treatment under different controlled atmospheres. The aim was to explore the modifications that annealing can induce in defects, subsequently affecting structural, morphological, optical, and electrical attributes. The thermal treatment of the Co3O4 films was carried out under controlled atmospheres such as Ar, N2, O2, and synthetic air. After tuning the excitation energies, we performed photoconductivity measurements that provided insights into the optical absorption edges of the oxide (Co2+ and Co3+). We also evaluated the effect of different atmospheres on photoconduction measurements. Inherent defects within ZnO result in charge compensation effects and play a role as transport traps when exposed to light excitation. Sodium doping triggers a conductivity switch from n-type to p-type within specific temperature ranges. Photoconductivity measurements of ZnO:Na films were conducted using excitation above the material's absorption edge. In this scenario, the sample containing 10% Na displayed the most remarkable photoresponse. Annealing in different atmospheres shows significantly faster responses of the highly transparent films in visible light. Additionally, we analyzed the resistive memory effects of the ZnO doped with 10% sodium as well as the influence of the atmosphere on the film's memristive responses.